FACTORS FOR THE ESTABLISHMENT AND DEVELOPMENT OF SMALL INDUSTRIAL ZONES - Salimov B. B; Arslanbekov S. M (Research Parks Publishers, 2021)
This paper makes analyses of the factors for the establishment and development of small industrial zones. On this case, research investigates both theoretical and methodological. Finally, it makes conclusion of outcomes and shortcomings of the issue.